O desafio da seleção de pessoal estratégica no setor público: análise das limitações dos concursos públicos na avaliação das competências dos canditatos - Josimar Martineli Teixeira (2019)
One of the great challenges to be faced in public organizations refers to the strategic selection of servers with the technical and behavioral skills necessary for the good performance of the activities. In this sense, it is fundamental that the process of selection of personnel in the public sector be effective and use methods that can assertively identify the most suitable candidates for public office, thus improving the effectiveness and quality of the services provided by the Public Administration. However, despite the importance of selective processes for the effectiveness of public management, it should be noted that public tenders, the main selection process, still present some limitations in personnel selection, which directly affect the effectiveness of the public sector. Therefore, the present research had as objective to analyze the limitations of the public tender in the evaluation of the competences of the candidates. For this, a descriptive research was carried out regarding its nature, qualitative as to its purposes and documentary research as to its means. Twenty-nine public tenders published in the last ten years, between 2009 and 2018, were analyzed in the city of Belo Horizonte in the state of Minas Gerais. The results of the research indicate that the main limitations of public recruitment in personnel selection are related to the stages of the selection process, in which the evaluation of academic and intellectual competences is predominant, disregarding other competences that are necessary to choose the candidate with the most appropriate profile for the position.